Movement of Southern Elephant Seals (Mirounga leonina L.) from Elephant Is. South Shetlands, Antarctica - Muelbert, Monica Mathias Costa (2004)
In 1999, at-sea activity of two young southern elephant seal males (Mirounga leonina) from Elephant Is.(61°13’S,55°23’W), Antarctica, was monitored and tracked for 9 months. The individuals were randomly selected, captured,sedated (Zoletil 50®- 1mg/kg), weighed, measured, bled, paint-marked and fitted with satellite tags (STDR - ST- 6PPT, Telonics®, USA). Deployment of the STDR took about 45 min since each animal had a lower incisor tooth extracted for age determination. The seals exhibited individual behaviors. Seal “V”-23842 (BM ~ 801kg) moved from Elephant Is. (61.2ºS 55.3ºW) in Jan. 1999 to King George Is. (62.2ºS 58.1ºW) in Feb. 1999 when the tag stopped signaling. Seal “T”-23843 (BM ~ 656 kg) was restricted to the area around Elephant Is. (61.2ºS 54.4ºW -61.6ºS 55.4ºW) from January to May 1999, when it started to move south-eastwards. Although the age of these individuals was not yet determined it was likely to explain the difference in the two patterns of movement reported here. The temporal and spatial association of these movements with areas of high productivity is being investigated to assess whether the observed distribution reflects foraging activity.